Meet the howlers! - Sayre, April Pulley (Charlesbridge, 2010)
These rain forest dwellers are loud and sloppy. This playful poem brings howler monkeys to life in all their growly, barking glory. Extra facts within the text give readers the lowdown on these loudmouths.